Model Investigation of Jet Flow Inside Two-phase Ejector - Chen Liang Liu Jinghui Chen Jiangping Chen Zhijiu (Zhileng xuebao)
The jet flow development inside an ejector in a compression/ejection refrigeration cycle was investigated.The flow processes along the flow path inside the ejector were modeled including pressure adjustment,jet mixture,equalization,and diffusion.The computing results are well consistent with the experimental data.The entrainment ratio,outlet pressure,and energy-saving effect increase with the increase in condensing temperature in the compression/ejection refrigeration cycle.Moreover,there is an optimum evap...